The Heat Transfer Coefficient in a Copper Pipe Flow System Using a 40/60 Volume Ratio Ethylene Glycol/Water (EG/H2O) Blended Fluid - Thiyana, Thyana; Junaedi, Ahmad; Rahman, Mumammad Arif; Sukarman, Sukarman; Khoirudin, Khoirudin; Azizah, Renata Lintang (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
This study discusses the performance of Ethaline Glycol/water (EG/H2O) fluids at a volume ratio of 40/60. EG/H2O fluids are widely used as basic fluids in cooling and heating system applications. The discussion of EG/H2O fluid performance is focused on the analysis of the heat transfer coefficient and pressure drop. The study used an experimental method using a suction test made of pure copper with an inner diameter, outer diameter and length of 16 mm, 19 mm and 1500 mm respectively. The EG/H2O volume ratio at 40/60 was selected as the input parameter. Other input parameters are variations in the fluid flow rate which are regulated using a control valve at fluid flow rates of 4, 6, 8, 10.12, 14.16 and 18 liters/minute. A 2-unit tubular heater with a total capacity of 2000 W was installed on the sides of the copper pipes. A voltage regulator with a capacity of 3000 W is used to regulate the electric power by regulating the supplied voltage. Ampere pliers are used to measure amperage at the setting used. The experimental results show that the performance of the EG/H2O fluid on the heat transfer coefficient increases as the fluid flow rate increases. The highest heat transfer coefficient rate was obtained at a fluid flow rate of 18 L/minute, while the lowest value was obtained at a fluid flow rate of 4 L/minute. Pressure drops fluctuations occur as the fluid flow rate increases. Even though there is a fluctuating pressure drop, this condition does not significantly affect the friction factor, because the fluid flow characteristics occur in a turbulent manner